Pemanfaatan Ekstrak Daun Sirih Hijau (Piper Betle Linn.) sebagai Capping Agent dalam Green Synthesis Spinel Ferit ZnFe2O4 untuk Remediasi Fenol dalam Air dan sebagai Anti Bakteri - Rahmayeni, Rahmayeni; Yuliani, Putri; Putri, Yulia Eka; Stiadi, Yeni (Universitas Andalas, 2024)
The spinel ferrite material ZnFe2O4 was synthesized using a green synthesis approach by the hydrothermal method. In the synthesis, 2M NaOH was used as a mineralizer and betel leaf extract with varying volumes of 1, 3, 5, and 7 mL as a capping agent, then continued with calcination at 500, 600, and 700°C. Several devices, such as XRD, FT-IR, SEM-EDX, DRS-UV-Vis, and VSM, were used to characterize the synthesized ZnFe2O4 material. The pattern of XRD indicated that the ZnFe2O4 material has a cubic structure, where the increase in crystal size was after calcination. The Fourier Transform Infra-Red (FT-IR) spectrum shows the Fe-O interaction at wave numbers 427-417 cm-1, which is located on the octahedral side, while the Zn-O interaction at wave numbers 534-510 cm-1, which is located on the tetrahedral side in spinel ferrite structure. From the DRS UV-Vis spectrum pattern and band gap values, it was found that the material absorbs light in the visible region. Scanning Electron Microscope (SEM) images show that the morphology of the synthesized material is circular. The Vibrating Sample Magnetometer (VSM) hysteresis curve shows that the synthesized ZnFe2O4 has paramagnetic properties. The synthesized ZnFe2O4 material has photocatalytic activity towards phenolic compounds with a degradation percentage reaching 62.2%, and this material is active as an antibacterial with an inhibition area of 14.4 for S. aereus bacteria.